Character self-construction and moral principles – general theoretical framework - Mamali, Cătălin (Filozofia Publiczna i Edukacja Demokratyczna, 2015)
The study starts from the premise that within the dynamic of personality system character is mainly an acquired subsystem that is the outcome of self and social construction. On a continuum that represents the interaction between innate and acquired factors the study posits that character is mostly constructed while temperament is mostly given. The research is focused on long-term personal experiences that aimed explicitly to develop one’s own character. Taking into account the theoretical framework of Petersen and Seligman (2004) that distinguishes between strengths and virtues the present model of character includes three dimensions and an orienting principle. The three dimensions are: a) strength-weakness; b) goodness-evilness; c) transparency versus opacity. A strong character could be good or evil, transparent or opaque. All these dimensions are related to self-tested orienting principles such as (Truth, Love, Justice, Non-violence).